Tumor characteristics and oncologic outcome after radical prostatectomy in men 75 years old or older - Mandel, Philipp; Kriegmair, Maximilian (The journal of urology, 2016)
Purpose: As life expectancy increases, oncologic outcome in elderly patients 75 years old or older is a salient topic requiring further investigation. Materials and Methods: We analyzed the records of 13,997 patients who underwent radical prostatectomy from 2006 to 2013. Known prognosticators were compared according to age at radical prostatectomy in 13,732 patients younger than 75 years vs 265 patients 75 years old or older. Univariate and multivariate Cox regressions were used to estimate the impact of age on biochemical recurrence-free, metastasis-free, cancer specific and overall survival. Results: Median followup was 47.3 months. Compared to patients younger than 75 years those 75 years old or older had a higher pathological Gleason score (p < 0.001) and were more likely to harbor a nonorgan confined tumor (p < 0.001), have a positive surgical margin (p = 0.004) and positive lymph nodes (p = 0.028), and receive salvage androgen deprivation therapy (p = 0.002). Five-year biochemical recurrence-free, metastasis-free, cancer specific and overall survival rates were 64.2%, 84.7%, 98.4% and 91.3% in patients 75 years old or older, and 76.9%, 96.2%, 99.0% and 96.2%, respectively, in patients younger than 75 years. On univariate and multivariate analysis age 75 years or greater was associated with worse biochemical recurrence-free and metastasis-free survival. Patients 75 years old or older were more likely to die of other causes than cancer. Nevertheless, noncancer related mortality was low. Conclusions: Older patients who underwent radical prostatectomy had more advanced disease. Age itself is an independent predictor of worse biochemical recurrence-free and metastasis-free survival. Healthy and highly selected patients 75 years old or older in our sample showed good long-term overall survival. Therefore, older age in well selected men should not be a contraindication to radical prostatectomy, especially in patients harboring high risk disease.
Gesehen am 08.07.2019